COGNITIVE MODELS AND NEUROMARKETING: UNVEILING THE PSYCHOLOGICAL FOUNDATIONS OF CONSUMER PURCHASING BEHAVIOUR - Yuli Purbaningsih; Risnawati Ramli; Sartika S; Prisilia Angel Tantri; Nina Triolita (CV. Adiba Aisha Amira, 2025)
This study comprehensively explores consumer purchasing behavior by synthesizing cognitive models and neuromarketing principles. Navigating the intricate dynamics between conscious and unconscious processes, it investigates classical cognitive models, notably the Information Processing Model, and contemporary theories like the Dual Process Theory. Venturing into the transformative landscape of neuromarketing, the study uncovers the neural correlates and neurotransmitter influences shaping consumer choices. Ethical considerations and methodological limitations are rigorously examined to provide a balanced understanding. Furthermore, the study outlines future directions, emphasizing the contemplation of emerging technologies and encouraging interdisciplinary collaborations. The findings offer profound insights, enriching current knowledge, shaping consumer behavior research trajectory, and revolutionizing future marketing strategies.